EFFECT OF Centella asiatica AND Nigella sativa EXTRACTS AS ANTICONVULSANTS IN PENTYLENETETRAZOLE-INDUCED EPILEPSY MODEL - Rambe, Avie Hanindya Dwiyanti; Batubara, Chairil Amin; Fitri, Aida (MNJ (Malang Neurology Journal), 2026)
Background: Epilepsy is a neurological disorder that is still widely found. The main goal of epilepsy therapy is for epilepsy patients to achieve an optimal quality of life with minimal therapeutic side effects. The active compounds in Centella asiatica and Nigella sativa have shown anticonvulsant effects. Objective: To determine the difference in anti-convulsant effects on the administration of Centella asiatica and Nigella sativa extracts in pentylenetetrazole-induced acute epilepsy model. Methods: This experimental study was conducted using 28 male Swiss divided into 7 equally large groups. The study was conducted with CMC Na 0.5% as a negative control and oral Phenitoin 25mg/Kg as a positive control, and 5 treatment groups were given C. asiatica extracts 800mg/Kg and 1000mg/Kg, N. sativa 800mg/Kg and 1000mg/Kg, and a mixture of C. asiatica 400mg/Kg and N. sativa 400mg/Kg orally. On the 7th day, seizure induction with pentylenetetrazole was performed, then measurements were taken. Results: There was significant difference on the seizure onset (p<0.001). In the experimental group, the longest onset we found was in the C. asiatica extract 1000mg/Kg group (99.25 ± 42.96 seconds). There was a significant difference in the total duration of seizure in C. asiatica 1000mg/Kg (p=0.031), N. sativa 800mg/Kg (p= 0.041), and N. sativa 1000mg/Kg (p= 0.030) groups. Conclusion:  Administration of C. asiatica 1000mg/Kg and N. sativa 800 and 1000mg/Kg extracts had an anticonvulsant effect on the duration of seizures.